Occurrence of Eurasian Skylark Alauda arvensis territories in relation to urban area and heterogeneous farmland - Loretto, Matthias-Claudio; Schöll, Eva Maria; Hille, Sabine (My University, 2019)
Within heterogeneous arable habitats close to urbanized Vienna, Austria, Eurasian Skylarks Alauda arvensis occurred at slightly lower densities than in other mixed farmland areas and at a much lower density than would be found in natural habitats. Territory density was negatively correlated with the occurrence of roads, tracks and high-intensity agricultural cultivation, possibly due to the resulting increased disturbance by humans.
Keywords: 570